Once more, with feeling: Conductors' use of assessments and directives to provide feedback in choir rehearsals. (September 2019) - Emerson, Kathryn; Williamson, Victoria; Wilkinson, Ray
In this article Conversation Analysis is used to explore the way that conductors give feedback in choir rehearsals through the use of assessments and directives. Assessments and directives have previously been investigated in some forms of music teaching and rehearsing, although not in choir rehearsals. There is also a paucity of research on the methods by which a conductor may give feedback following an episode of singing by the choir. This analysis is based on 19 hours of choir rehearsal data, involving eight choirs and nine conductors. We show that conductors' feedback turns typically consist of two particular communicative behaviours: assessments and directives, either occurring singly or in various combinations. Assessments explicitly evaluate (positively or negatively) the just-produced singing of the choir, and directives explicitly tell the choir something about how members should sing in the future. However, the data reveal that assessments can also function implicitly to direct how the choir should sing, and directives can implicitly evaluate singing. Assessments and directives can be done in depicted forms (e.g., using sung vocalisations and gestures), as well as verbal descriptive forms. These findings highlight the distinctive ways that conductors produce feedback within rehearsals and some of the particular inferences that choir members must draw on to understand this feedback, as well as how change and improvement in the choir's singing may be affected on a turn-by-turn basis.